2013
DOI: 10.1186/1471-244x-13-222
|View full text |Cite
|
Sign up to set email alerts
|

Levels of autistic traits in anorexia nervosa: a comparative psychometric study

Abstract: BackgroundA number of characteristics associated with Autism Spectrum Disorders (ASD) are over-represented among patients with Anorexia Nervosa (AN) as well as among relatives of these patients. Yet the co-occurrence of autistic traits in AN has not been fully explored and no previous study has directly compared self-reported evaluations of cognitive and socio-affective skills in AN and ASD.MethodsWe aimed to determine the degree of overlap between AN and ASD from scores on questionnaires classically used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 53 publications
(61 reference statements)
6
46
0
Order By: Relevance
“…Despite the literature described (for example, [14,20-22]), this is in accordance with a psychometric study reporting that both AN and ASC groups demonstrated a need for sameness; however, other core features of autism, such as difficulty empathizing, were not seen in the AN group [56]. …”
Section: Discussionsupporting
confidence: 83%
“…Despite the literature described (for example, [14,20-22]), this is in accordance with a psychometric study reporting that both AN and ASC groups demonstrated a need for sameness; however, other core features of autism, such as difficulty empathizing, were not seen in the AN group [56]. …”
Section: Discussionsupporting
confidence: 83%
“…Taylor et al, 1988) to examine alexithymia in people with AN (Beales & Dolton, 2000;Berthoz, Perdereau, Godart, Corcos, & Haviland, 2007;Corcos et al, 2000;Deborde et al, 2007;De Panfilis, Rabbaglio, Rossi, Zita, & Maggini, 2003;Franzoni et al, 2013;Lawson et al, 2008;Marchesi, Ossola, Tonna, & De Panfilis, 2014;Torres et al, 2015; Appendix A for metaanalysis references). One study used the Bermond-Vorst Alexithymia questionnaire (Vorst & Bermond, 2001) which the authors report has a total score considered equivalent to that of the TAS (Courty et al, 2013). The TAS derives an overall score and three subscales difficulty identifying feelings, difficulty describing feelings, and externally oriented thinking.…”
Section: Emotional Awareness and Identificationmentioning
confidence: 99%
“…The findings of the studies using the Interpersonal Reactivity Index (Beadle et al, 2013;Calderoni et al, 2013) have been mainly inconclusive, with the study by Calderoni and colleagues (2013) revealing that AN patients reported less cognitive, but not affective empathy than controls, whereas the study by Beadle and colleagues (2013) found that AN patients demonstrated greater personal distress (a domain of affective empathy) compared to the controls. Of the few more recent studies Courty et al, 2013;Hambrook et al, 2008), that have utilized the EQ, only the study by Baron-Cohen and colleagues (2013) found that EQ scores were lower for AN patients compared to controls, however this finding was only obtained for the younger AN age group (aged 12 to 15 years).…”
Section: Empathisingmentioning
confidence: 99%